Impact of poverty and family adversity on adolescent health: a multi-trajectory analysis using the UK Millennium Cohort Study - Nicholas Kofi Adjei; Daniela K. Schlüter; Viviane S. Straatmann; Gabriella Melis; Kate M. Fleming; Ruth McGovern; Louise M. Howard; Eileen Kaner; Ingrid Wolfe; David C. Taylor-Robinson (Elsevier, 2022)
Summary: Background: Children exposed to poverty and family adversities including domestic violence, parental mental ill health and parental alcohol misuse may experience poor outcomes across the life course. However, the complex interrelationships between these exposures in childhood are unclear. We therefore assessed the clustering of trajectories of household poverty and family adversities and their impacts on adolescent health outcomes. Methods: We used longitudinal data from the UK Millennium Cohort study on 11564 children followed to age 14 years. Family adversities included parent reported domestic violence and abuse, poor mental health and frequent alcohol use. We used a group-based multi-trajectory cluster model to identify trajectories of poverty and family adversity for children. We assessed associations of these trajectories with child physical, mental and behavioural outcomes at age 14 years using multivariable logistic regression, adjusting for confounders. Findings: Six trajectories were identified: low poverty and family adversity (43·2%), persistent parental alcohol use (7·7%), persistent domestic violence and abuse (3·4%), persistent poor parental mental health (11·9%), persistent poverty (22·6%) and persistent poverty and poor parental mental health (11·1%). Compared with children exposed to low poverty and adversity, children in the persistent adversity trajectory groups experienced worse outcomes; those exposed to persistent poor parental mental health and poverty were particularly at increased risk of socioemotional behavioural problems (adjusted odds ratio 6·4; 95% CI 5·0 - 8·3), cognitive disability (aOR 2·1; CI 1·5 - 2·8), drug experimentation (aOR 2·8; CI 1·8 - 4·2) and obesity (aOR 1·8; CI 1·3 - 2·5). Interpretation: In a contemporary UK cohort, persistent poverty and/or persistent poor parental mental health affects over four in ten children. The combination of both affects one in ten children and is strongly associated with adverse child outcomes, particularly poor child mental health. Funding: The National Institute for Health Research (NIHR) Policy Research Programme, NIHR Applied Research Collaboration South London (ARC South London) at King's College Hospital NHS Foundation Trust and the Medical Research Council (MRC).